Propagation of gladiolo (Gladiolus grandiflorus) andr. cv. Snow Princess, through cormels types 7 and 8 - Mattos, J.R.; Simão, S.; Braga Jr., R.L.C.; Campos, H.; Moreira, C.S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
Cormels type 7 produced corms and cormels type 1 to 8 in greater quantity than type number 8 and corms type 1, 2, 3, 4 and 5 were heavier. Cormels type 8 also produced corms and cormels type 1 to 8, however their cormels were heavier than cormels produzed by type 7.